Achieving environmental sustainability through environmentally friendly technologies in OECD countries: The role of financial development - Visas, Hubert; Krivins, Anatolijs; John, Moti Wilson (Energy Economics Letters, 2023)
The issue of environmental degradation demands urgent action to mitigate its drastic effects on the economy. To overcome the challenge of climate change, countries around the globe have been devising strategies. Eco-innovation (EI) is a basis to achieve this target because it comprises many technologies and can help to control global warming. Considering the importance of EI, this study examines its impact on environmental performance in OECD countries over the period from 1990 to 2021. Advanced econometric approaches were used, which found that EI is a critical driver of environmental progress and exhibits a negative impact on carbon dioxide (CO2) emissions, highlighting its role in fostering environmental sustainability. Moreover, financial development (FD), often associated with capital allocation, supports a downward trend in emissions, signifying a synergy between robust financial systems and environmental responsibility. Countries with a well-developed financial infrastructure and a propensity for international trade are poised to reap the benefits from EI, owing to their capacity to readily embrace cutting-edge technological advancements. This study suggests that countries with highly developed finance systems have the ability to amplify the positive impacts of EI on environmental performance.